Determinants of Awareness on Diabetes and its Complications - Sendur, Umit Gokhan; Adas, Mine (Experimental and Clinical Endocrinology & Diabetes, 2019)
Introduction Diabetes mellitus is a chronic disease that requires continuous medical care. Raising awareness and determining the factors affecting awareness about diabetes and its complications have an important role in achieving glycemic control and preventing complications.Objective In this study, we aimed to determine the sociodemographic properties of participants, the status of patients’ awareness, and the factors affecting awareness. We also aimed to determine the relationships between these factors and diabetes regulation.Materials and Methods A total of 404 patients with diabetes who had presented to Istanbul Okmeydanı Research and Training Hospital, Internal Medicine and Diabetes Outpatient Clinic were included in the study. They were requested to fill in a questionnaire about diabetes awareness. Data about their survey results, sociodemographic facts, glycemic control, treatment methods, and complications were analyzed.Results 61.6% of the participants were female and 38.4% were male. Mean age was 54.5±11.4 years. 55.2% of patients were graduated from primary school and 22.8% had no education. Mean HbA1c value of the participants was 8%±1.9%. The mean score of the questionnaire, consisting of 23 questions, was 16.1±3.6. The ratio of patients who replied to 50% or more of the survey was 90.3%. The knowledge score was found to be positively correlated with education and income level, negatively correlated with age. There was no significant relationship between awareness and glycemic control (p>0.05).Conclusion Most of the participants had an adequate level of awareness on diabetes and its complications. However, the study showed that better awareness was not associated with regulation of the disease. It was observed that not only raising awareness but also methods for implementing knowledge to daily life are needed.
Keywords: awareness; diabetes mellitus; glycemic control; related factors